Common Mistakes Found in Essay Writing of Chemical Engineering Department First Grade Students in Politeknik Negeri Lhokseumawe - Marzuki, Marlina (Universitas Malikussaleh, 2019)
Many students often face difficulties when they are writing an essay in English while they are required to master written English as one of their basic competencies as the vocational students. The study observes common mistakes occurring in English essays written by first grade students of Oil and Gas Processing Study Program of Chemical Engineering Department in Politeknik Negeri Lhokseumawe, Aceh, Indonesia. The mistakes were categorized into seven types, i.e. word collocation and phrase, preposition, article/determiner, verb form, word order, spelling and punctuation. This research aims to find out the relation between the occurrences of the mistakes to the background of the students as the non-native English speaker. The methodology used in this study was combined between descriptive analysis and quantitative method. Data were analyzed by calculating the mistakes number done the students in their essays. The percentage of each mistake parameter is presented in pie chart form. Twenty-two students were involved in this study. Based on the result found in the study, the writer has gained several points that can be used to improve the teaching material for writing for academic purpose course. The study suggests that the course should focus on word collocation and some basic grammars instead of giving them English text.